Ulama dan Demokrasi: Studi Peran Tokoh Ulama dalam Pemilu Presiden 2024 - Fatimah, Nurul; Yusrul Hana, Muhamad (FIHROS: Jurnal Sejarah dan Budaya, 2025)
This study aims to analyze the role of ulama (Islamic scholars) in Indonesian democracy, specifically in the context of the Pemilu Presiden 2024 , by examining the historical dynamics of ulama involvement in politics from the Old Order to the Reformation era. The research method used is a literature study with a qualitative approach, employing phenomenology theory and Foucault's historical genealogy. The results show that the role of ulama in Indonesian politics is influenced by political changes, social movements, and religious principles. In the Pemilu Presiden 2024, ulama were involved in various forms of support, including public support and declarations, mass mobilization, influencing public opinion, bestowing titles and honors, and practical political roles. However, this involvement also poses challenges, such as polarization and the potential for religious misuse. Ulama are required to maintain neutrality and use social media wisely. Nevertheless, the role of ulama in Indonesian democracy has positive impacts, such as increasing political awareness and instilling moral values. Yet, negative impacts such as polarization and potential religious manipulation must be heeded. History notes that the ulama's role is always dynamic, influenced by political changes and religious principles.